The biogeography and filtering of woody plant functional diversity in North and South America - Nathan G. Swenson; Brian J. Enquist; Jason Pither; Andrew J. Kerkhoff; Brad Boyle; Michael D. Weiser; James J. Elser; William F. Fagan; Jimena Forero‐Montaña; Nikolaos Fyllas; Nathan J. B. Kraft; Jeffrey K. Lake; et al. (Global Ecology and Biogeography, 2012)
Aim In recent years evidence has accumulated that plant species are differentially sorted from regional assemblages into local assemblages along local‐scale environmental gradients on the basis of their function and abiotic filtering. The favourability hypothesis in biogeography proposes that in climatically difficult regions abiotic filtering should produce a regional assemblage that is less functionally diverse than that expected given the species richness and the global pool of traits. Thus it seems likely that differential filtering of plant traits along local‐scale gradients may scale up to explain the distribution, diversity and filtering of plant traits in regional‐scale assemblages across continents. The present work aims to address this prediction. Location North and South America. Methods We combine a dataset comprising over 5.5 million georeferenced plant occurrence records with several large plant functional trait databases in order to: (1) quantify how several critical traits associated with plant performance and ecology vary across environmental gradients; and (2) provide the first test of whether the woody plants found within 1° and 5° map grid cells are more or less functionally diverse than expected, given their species richness, across broad gradients. Results The results show that, for many of the traits studied, the overall distribution of functional traits in tropical regions often exceeds the expectations of random sampling given the species richness. Conversely, temperate regions often had narrower functional trait distributions than their smaller species pools would suggest. Main conclusion The results show that the overall distribution of function does increase towards the equator, but the functional diversity within regional‐scale tropical assemblages is higher than that expected given their species richness. These results are consistent with the hypothesis that abiotic filtering constrains the overall distribution of function in temperate assemblages, but tropical assemblages are not as tightly constrained.